Strategi Pembinaan Warga Gereja untuk - Tupa Pebrianti Lumbantoruan; Andreas Yonatan Gultom (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
This research aims to examine and research usually includes several important sections that explain the topic of discussion or research. This abstract begins with an explanation of the background of the problem: The role of youth in the church and their role as the next generation. They have great potential to vitalize church ministries and realize the mission of the church around the world. However, often this potential is not well developed due to a lack of proper guidance.Next, the abstract provides an explanation of the purpose of the discussion or research. To help church youth discover, develop, and utilize their potential in church ministry and community life, the author attempts to create an effective coaching strategy. This strategy is intended to form youth who are not only intellectually skilled but also spiritually, emotionally, and socially mature. It often contains several important components that explain the Abstract and ends with a conclusion that emphasizes how important youth development is as part of church ministry. A church that is able to develop the potential of the younger generation has a positive effect on society as a whole. This abstract emphasizes that successful coaching strategies rely heavily on cooperation between church leaders, families, and the church community in creating an environment that supports overall growth.